2013
DOI: 10.1002/ep.11798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foam agent on characteristics of thin‐film transistor liquid crystal display waste glass‐metakaolin‐based cellular geopolymer

Abstract: Thin‐film transistor liquid crystal display (TFT–LCD) waste glass comprises mainly SiO2 and Al2O3, which are suitable raw materials for geopolymer. This study investigates the effects of the amount of foam agents on the properties of waste glass‐based cellular geopolymer. In this investigation, samples underwent a series of tests to determine their quality, including mechanical characterization, compressive strength, flexural strength, fire resistance, thermal conductivity, Fourier transform infrared spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…For the geopolymer, the broad band from 3658 to 3180 cm −1 detected in the spectra can be assigned to stretching vibration of structural water and free water, and the small bands at 1651 and 714 cm −1 is attributed to the bending vibration of free water [14,31,33]. The occurrence of new correlative characteristic bands, the disappearance of the band at 802 cm −1 , and the obvious shift of the center of broad bands from about 1080 toward 1002 cm −1 , compared with pure MK, jointly indicated the proceeding of the geopolymerization reaction and setting [14,[30][31][32]. The new weak intensity of band located at 1392 cm −1 is assigned to the vibration of the C-O bond of carbonate groups by the atmospheric carbonation of the alkaline cations [32].…”
Section: X-ray Diffraction and Infrared Spectroscopy Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…For the geopolymer, the broad band from 3658 to 3180 cm −1 detected in the spectra can be assigned to stretching vibration of structural water and free water, and the small bands at 1651 and 714 cm −1 is attributed to the bending vibration of free water [14,31,33]. The occurrence of new correlative characteristic bands, the disappearance of the band at 802 cm −1 , and the obvious shift of the center of broad bands from about 1080 toward 1002 cm −1 , compared with pure MK, jointly indicated the proceeding of the geopolymerization reaction and setting [14,[30][31][32]. The new weak intensity of band located at 1392 cm −1 is assigned to the vibration of the C-O bond of carbonate groups by the atmospheric carbonation of the alkaline cations [32].…”
Section: X-ray Diffraction and Infrared Spectroscopy Analysismentioning
confidence: 88%
“…The characteristic bands of MK can be clearly observed at 1080, 802, 566, and 460 cm −1 [14,-29-32]. The strong broad band with wavenumber centered at 1080 cm −1 is related to the stretching vibration of Si-O-Al and Si-O-Si [14,30], and previous works reported that this broad band from 1200 to 1000 cm −1 is caused by the overlapping of bands derived from dehydroxilated pyrophyllite [29,31]. Furthermore, the band at 802 cm −1 corresponds to the O-Al-O bending vibrations of AlO 4 tetrahedra [29,31], and the band with low intensity detected in the spectrum at 566 cm −1 belongs to the Si-O-Al bond in octahedral coordination [14,30].…”
Section: X-ray Diffraction and Infrared Spectroscopy Analysismentioning
confidence: 99%
“…Chemical composition: X-ray fluorescence (XRF) analysis was performed using an automated RIX 2000 spectrometer. Specimens were prepared for XRF analysis by mixing 0.4 g of sample and 4 g of 100 Spectroflux at a dilute ratio of 1:10 [40]. The homogeneous mixtures were placed in Pt-Au crucibles before being heated for 1 h at 1000°C in an electric furnace.…”
Section: Methodsmentioning
confidence: 99%
“…A numbers of techniques can be employed to create pores in concrete. One of simplest and the most effective techniques is to add air entrainment agents such as aluminium powder [16]- [19], metallic silicon [20]- [21] and hydrogen peroxide [22]- [23].…”
Section: Effects Of Aluminium Addition On Inhibition Of Concrete Expansion Resulted From Alkali Silica Reaction (Asr) 1 Introductionmentioning
confidence: 99%